Kualitas hidup pasien diabetes melitus dengan tuberkulosis: Literatur review - Rissaadah, Siti; Sulastini, Sulastini; Widadi, Sri Yekti; Setiowati, Rahayu; Sriwahyuni, Sriwahyuni; Sugiharto, Firman; Alia, Fania Putri (Published by: Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Persatuan Perawat Nasional Indonesia (PPNI), 2025)
Abstract Background: Diabetes mellitus (DM) is a chronic disease with a steadily increasing prevalence globally. DM is often associated with a decreased quality of life, especially if comorbidities such as tuberculosis (TB) occur. Uncontrolled hyperglycemia in diabetes can suppress the immune system, increasing the risk of TB infection. Purpose: To evaluate the quality of life of DM patients with TB based on physical, psychological, and social domains through a narrative review approach. Method: Articles used in this study were identified through the PubMed, Scopus, and EBSCHO databases. The literature search used the keywords